DESIGN AND PREPARATION OF THIN FILM GEL POLYMER ELECTROLYTE FOR 3D LI-ION BATTERY - Tolganbek, Nurbol; Mentbayeva, Almagul; Serik, Nurassyl; Batyrgali, Nursaule; Naizakarayev, Miras; Kanamura, Kiyoshi; Bakenov, Zhumabay (Elsevier B.V., 2021)
Three-dimensional (3D) configuration of the battery provides a large active surface area of the electrodes to store and utilize more active material, enabling remarkable increase of capacity. Herein, we report on the development of a full 3D battery composed of Ni3Sn4 (Ni–Sn) alloy electrodeposited onto a nickel foam current collector to form a 3D anode, which was coated with a polymer electrolyte-separator film, and LiFePO4/CNT cathode filled into the voids of the resulting 3D structure. An ultrathin polymer coating on the 3D anode was obtained via layer-by-layer technique. The X-ray diffraction investigations confirmed stability of the structure of the anode prior and after the polymer coating, while top and cross-section SEM images proved the uniformity of both the deposited 3D anode and the polymer coating on its surface. It was shown that a thin homogeneous layer of polymer can be obtained on 3D structured anode. This film effectively performed as a gel-like electrolyte in a full 3D battery. Cyclic voltammetry and charge-discharge tests exhibited stable electrochemical response and cyclability of the 3D battery. The prepared full 3D battery successfully operated at 0.1C rate and retained 90% of its initial capacity over 100 galvanostatic charge-discharge cycles.
Keywords: 3D battery; Anode; Gel electrolyte; Ni–Sn alloy; Lithium-ion battery (LIB); Type of access: Open Access